2018
DOI: 10.1377/hlthaff.2017.1427
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Test Availability And Spending: Where Are We Now? Where Are We Going?

Abstract: Genetic testing and spending on that testing have grown rapidly since the mapping of the human genome in 2003. However, it is not widely known how many tests there are, how they are used, and how they are paid for. Little evidence from large data sets about their use has emerged. We shed light on the issue of genetic testing by providing an overview of the testing landscape. We examined test availability and spending for the full spectrum of genetic tests, using unique data sources on test availability and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
125
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 184 publications
(132 citation statements)
references
References 11 publications
(14 reference statements)
4
125
0
3
Order By: Relevance
“…25 The decrease also likely coincides with gaining popularity of multiple-gene panel tests and direct-to-consumer genetic testing (which were not captured in this study). [26][27][28][29] Our findings are consistent with a recent study by Lynch and colleagues of Medicare beneficiaries, which showed that CYP pharmacogenetic tests were the most common tests received by this group in 2013. 30 Likewise, "long-term (current) use of other medication" was the most common diagnosis for CYP pharmacogenetic tests among both Medicare cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…25 The decrease also likely coincides with gaining popularity of multiple-gene panel tests and direct-to-consumer genetic testing (which were not captured in this study). [26][27][28][29] Our findings are consistent with a recent study by Lynch and colleagues of Medicare beneficiaries, which showed that CYP pharmacogenetic tests were the most common tests received by this group in 2013. 30 Likewise, "long-term (current) use of other medication" was the most common diagnosis for CYP pharmacogenetic tests among both Medicare cohorts.…”
Section: Discussionsupporting
confidence: 91%
“…The use of NGS tests (including multigene panels, whole exome, and whole genome sequencing) has been increasing. (1) However, only a limited number of studies have examined their economic value. (2) Several studies have noted that there are methodological challenges to evaluating NGS tests that may be a barrier to conducting evaluations.…”
Section: Introductionmentioning
confidence: 99%
“…There are currently more than 70,000 unique genetic testing products on the market and an average of 10 new products are added each day (36). The market for clinical sequencing - which encompasses the use of sequencing tests for diagnosis, risk prediction, therapy selection and monitoring, and screening - is growing at a compound annual rate of 28% (37). …”
Section: Precision Medicine – Where Are We Today?mentioning
confidence: 99%